A bi-level optimization for a make-to-order manufacturing supply chain planning: a case in the steel industry. Issue 4 (2nd October 2021) - Ocampo, Lanndon A.; Vasnani, Neelesh N.; Chua, Felixter Leone S.; Pacio, Lance Brandon M.; Galli, Brian J.
Abstract : This paper presents an actual case application of a newly developed game-theoretic model in analyzing a single manufacturer-many supplier, multi-period, make-to-order supply chain with fuzzy parameters. The supply chain under consideration comprises an exclusive supplier for every component required by the manufacturer in producing its product. In certain instances, some supply chains enable the manufacturer to opt for a third-party subcontractor to produce a portion of its demand. We assume that the supply chain faces a price and lead-time-sensitive demand, which is relevant in a make-to-order environment. The vertical interaction within the supply chain is played as a Stackelberg game, where the manufacturer is considered the leader and the suppliers as the followers. Results show some important managerial insights in supply chain planning under a make-to-order condition.